1994
DOI: 10.1007/bf00017623
|View full text |Cite
|
Sign up to set email alerts
|

The diet and growth of roach (Rutilus rutilus (L.)) in Lake Vesij�rvi and possible changes in the course of biomanipulation

Abstract: Previous studies have suggested that the roach Rutilus rutilus (L .) stock of Lake Vesijarvi is one of the main factors delaying the recovery of the lake after sewage diversion . This study is concerned with the documentation of the diet of roach in the lake . In total, 531 roach were examined . Both in the pelagial and in the littoral the roach had mixed diets in May and in September-October . The importance of zooplankton decreased and the importance of benthos and plants increased with increasing size of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 22 publications
6
31
0
Order By: Relevance
“…Our results, however, indicate that there are age differences, with one-year-old fish consuming mainly detritus and zooplankton and older fish showing a significant preference for detritus, macrophytes, and periphyton. Age differences have also been observed by Horppila (1994), who found that the importance of zooplankton decreased and that of benthos and plants increased, with increasing roach size. Similarly, Volta and Jepsen (2008) observed a clear age difference when comparing diet of in shallow and deep reservoirs, with young roach consuming mainly algae and older specimens consuming mainly zooplankton, detritus and macrozoobenthos.…”
Section: Discussionsupporting
confidence: 53%
“…Our results, however, indicate that there are age differences, with one-year-old fish consuming mainly detritus and zooplankton and older fish showing a significant preference for detritus, macrophytes, and periphyton. Age differences have also been observed by Horppila (1994), who found that the importance of zooplankton decreased and that of benthos and plants increased, with increasing roach size. Similarly, Volta and Jepsen (2008) observed a clear age difference when comparing diet of in shallow and deep reservoirs, with young roach consuming mainly algae and older specimens consuming mainly zooplankton, detritus and macrozoobenthos.…”
Section: Discussionsupporting
confidence: 53%
“…Comparing the composition of the diet with the structure of macroinvertebrate assemblages, roach feed on those macroinvertebrate taxa in the Žeimena River which are the most abundant. Contribution of different taxa to the diet changes together with the size of individuals, and this is in line with known general pattern (Horppila, 1994;Jamet et al, 1990). The overall diversity of food items in the diet of roach in the moderately polluted Mūša River is greater, but plant material forms a major part of the food and was consumed most frequently irrespective of the size of roach individuals, although abundance of many macroinvertebrate taxa on which roach feed is nearly twice greater than that in the Žeimena River.…”
Section: Discussionsupporting
confidence: 85%
“…According to Horppila (1994), the frequent use of plant food indicates a low availability of animal prey. But this cannot be an explanation in case of the Mūša River, where macroinvertebrate taxa are numerous and diverse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…neither by external-nor sediment-derived phosphorus inputs (Kairesalo, et al, 1995;Hartikainen et al, 1996). This phosphorus increase, however, coincided with the early-summer migration of adult roach populations from the littoral areas to the pelagic zone (Peltonen & Horppila, 1992;Horppila 1994b). During 1989-93, these migrating fish, in particular, were the target of the trawlings which led to a dramatic reduction in their biomass; from 172 kg ha −1 (i.e.…”
Section: Ecological Basis For the Management Of Lake Vesijärvimentioning
confidence: 99%